1973
DOI: 10.1111/j.1550-7408.1973.tb06012.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Contractile Vacuole in the Osmoregulation of Tetrahymena pyriformis*

Abstract: SYNOPSIS The relationship of cell size and contractile vacuole efflux to osmotic stress was studied in Tetrahymena pyriformis strain W, after transfer into fresh solutions iso‐ or hypoosmotic to the growth medium. Microscopic measurements of the cell and contractile vacuole dimensions, made with an image‐sharing ocular at 27 C, allowed the calculation of the cell size and shape and the vacuolar efflux rate which provide a measure of osmoregulation. The contractile vacuole cycles have no homeostatic oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A quantitative estimate of vacuolar output must take account of the frequency of expulsions and of the amount of fluid expelled at each expulsion. This is because the amount of fluid expelled at each expulsion is not constant, nor is there any fixed relationship between frequency of expulsions and the rate of vacuolar output (Rifkin, 1973;Ahmad & Couillard, 1974; Patterson, 1976a). The size of the vacuole can be measured with any of a variety of measuring microscope oculars, but the most suitable for this purpose are imageshearing oculars (Rifkin, 1968).…”
Section: ( C ) Observation Of Contractile Vacuolesmentioning
confidence: 99%
See 2 more Smart Citations
“…A quantitative estimate of vacuolar output must take account of the frequency of expulsions and of the amount of fluid expelled at each expulsion. This is because the amount of fluid expelled at each expulsion is not constant, nor is there any fixed relationship between frequency of expulsions and the rate of vacuolar output (Rifkin, 1973;Ahmad & Couillard, 1974; Patterson, 1976a). The size of the vacuole can be measured with any of a variety of measuring microscope oculars, but the most suitable for this purpose are imageshearing oculars (Rifkin, 1968).…”
Section: ( C ) Observation Of Contractile Vacuolesmentioning
confidence: 99%
“…However, the case for this is weakened by two observations. First, the contractile vacuole continues to function in deionized water (Reuter, 1963; Raze & Schoffeniels, 1965; Rifkin, 1973). Second, in high potassium media, transient changes in the cellular potassium levels of some species follow an increase in the external osmotic pressure (with sucrose) (Kramh~rft, 1970; Patterson, 1976a;Kirst, 1977).…”
Section: ( 3 ) Ion Regulation Monovalent Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, thermal stress might result in increased cell metabolism and motility (Jacob & Legrand, 2021; Luan et al, 2012), which might increase dispersal rate. On the contrary, response to osmotic stress involves mechanisms such as glycerol production or regulation of intracellular sodium concentration (Dunham, 1964; Rifkin, 1973) that might trade‐off against dispersal ability.…”
Section: Discussionmentioning
confidence: 99%
“…However it has been observed that water influx to the vacuole is the most important form of osmoregulation (Rifkin 1973).…”
Section: Protozoamentioning
confidence: 99%